Shear Behavior of Reinforced Concrete Beams with Different Arrangements of Externally Bonded Carbon Fiber-Reinforced Polymer - Majid Faissal Jassim; Yousif Jabbar Lafta; Hawraa S. Malik (Journal of Engineering)
Carbonfiber-reinforced polymer (CFRP) composites are frequently utilized in the repair and reinforcement of reinforced concrete members because they are more corrosion-resistant, durable, and flexible than commonly used materials like steel plates. Many studies have demonstrated that the use of CFRP as an internal strengthening material has a substantial impact on the shear capacity of RC beams. This research looks into the possibility of using FRP material as an externally bonded reinforcement to increase the shear strength of RC beams. Because shear improvement and mode of failure are based on the right configuration of the CFRP sheets, the experimental work consisted of eight RC beams with various types, orientations, and configurations of CFRP sheets. All beams were examined under two-point bending. The test results show that the CFRP sheet significantly improved the beam’s shear strength and ductility and that it is advantageous to orient the FRP at 45 degrees to the beam’s longitudinal axis.